Preparing for College Success: Exploring Undergraduate Students' Perceptions of the Benefits of a College Reading and Study Skills Course through Action Research - Christy M. Howard; Lanette Moret; Johna Faulconer; Tanya Cannon; Amanda Tomlin (Networks: An Online Journal for Teacher Research, 2018)
The purpose of this study was to examine undergraduate students’ perceptions of the benefits of a college reading and study skills course. Researchers have found that even with increased emphasis on college readiness, many students continue to enter college unprepared for the rigorous academic expectations they may face. With this in mind, this study was designed to examine the perceptions of students entering college and being enrolled in a “support” course based on their SAT scores. Findings revealed that participants valued learning study skills and strategies that supported their understanding of course material before, during, and after the reading process. In addition, participants valued strategies that would transfer across courses in the university setting. This action research study provides the opportunity to consider how instructors can support students’ experiences in support courses through resources and strategies to support student success in college and beyond.
Keywords: college readiness; study skills; strategies; transfer of knowledge